Impact of the Americans With Disabilities Act Amendments Act on Documentation for Students With Disabilities in Transition to College: Implications for Practitioners. (February 2019) - Keenan, Walter R.; Madaus, Joseph W.; Lombardi, Allison R.; Dukes, Lyman L.
The Americans With Disabilities Act Amendments Act of 2008 expanded the legal definition of disability to establish broader coverage for individuals with disabilities, including college students, than the definition in the Americans With Disabilities Act of 1990. The new interpretation of the definition of disability shifted the main purpose of documentation from proving eligibility for services as a person with a disability to determining appropriate academic accommodations. This change in the law, and subsequent Department of Justice regulations, enhances the importance of documentation from a student's secondary education experience that may provide relevant information concerning functional limitations and the need for academic accommodations. This article provides practical guidance to high school professional staff in preparing disability documentation for students' transition to college.